The role of histone methylase and demethylase in antitumor immunity: A new direction for immunotherapy - Zhang, Yuanling; Chen, Junhao; Liu, Hang; Mi, Rui; Huang, Rui; Li, Xian; Fan, Fei; Xie, Xueqing; Ding, Jie (Frontiers in Immunology, 2023)
Epigenetic modifications may alter the proliferation and differentiation of normal cells, leading to malignant transformation. They can also affect normal stimulation, activation, and abnormal function of immune cells in the tissue microenvironment. Histone methylation, coordinated by histone methylase and histone demethylase to stabilize transcription levels in the promoter area, is one of the most common types of epigenetic alteration, which gained increasing interest. It can modify gene transcription through chromatin structure and affect cell fate, at the transcriptome or protein level . According to recent research, histone methylation modification can regulate tumor and immune cells affecting anti-tumor immune response. Consequently, it is critical to have a thorough grasp of the role of methylation function in cancer treatment. In this review, we discussed recent data on the mechanisms of histone methylation on factors associated with immune resistance of tumor cells and regulation of immune cell function.